Design and Ergonomics Analysis of Cutter Machine Locking Device in Aerospace Industry - Mat, Shafizal; Salim, Mohd Azli; Wan Mohd Farid , Wan Mohamad; Md. Saifuddin, Md Yusop (David Publishing Company, 2011)
Ergonomics has been used since 1850s and the application is widely used in aerospace industry, health care institution, information technology company, product design, transportation agency, training institution, nuclear engineering, virtual environmental and many more. Ergonomics is a science of designing the job, equipment and workplace to fit the workers environmental for more comfortable during the working duration. Since it related to the industry, this study is focused more to the mechanical device that is used at heavy aerospace engineering industry which is locking device design. This device is important to this industry because it is more related to safety procedure for workers during operation of certain machines. This study is aim on the improving the design of locking device for aerospace industry in term of ergonomics evaluation. Six conceptual designs were proposed and evaluated using scoring matrix technique. All of these designs were developed using computer aided design software and the highest score from the scoring matrix was proposed to replace the current device. Ergonomics analysis which is rapid upper limb assessment (RULA) is performed to evaluate the ergonomics design. From the analysis, it shows that the result of proposed design is better than existing design with highest score of 8 were reduced to score of 1 and 2. This means that the design is acceptable due to body posture of human parts from ergonomics evaluation.